2002
DOI: 10.1108/19355181200200001
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Privacy Policies in Fortune 500 Web Sites

Abstract: Although personal information privacy concerns have been around for years, the introduction of E-commerce and its associated technologies presents privacy concerns anew. The Fortune 500 represents traditional leadership in the use of technologies and business practices. This preliminary study examines Web sites of the Fortune 500 and shows that slightly more than 50 percent of Fortune 500 Web sites provide privacy policies on their home pages. Comprehensive privacy policies to address all privacy dimensions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…For example, the 1999 Gramm-Leach-Bliley Act for financial institutions requires that consumers be given the possibility to opt-out when the institution shares non-public information. A study by Liu & Arnett (2002) showed that 53.3% of Fortune 500 Web sites with privacy policies did not address opt-out concerns. As opposed to opt-out, the opt-in alternative permits the use of personal data within a firm, but first requires opt-in consent before information is disclosed to third-parties (Degryse and Bouckaert, 2006).…”
Section: Web Site Privacy Implementation Authormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the 1999 Gramm-Leach-Bliley Act for financial institutions requires that consumers be given the possibility to opt-out when the institution shares non-public information. A study by Liu & Arnett (2002) showed that 53.3% of Fortune 500 Web sites with privacy policies did not address opt-out concerns. As opposed to opt-out, the opt-in alternative permits the use of personal data within a firm, but first requires opt-in consent before information is disclosed to third-parties (Degryse and Bouckaert, 2006).…”
Section: Web Site Privacy Implementation Authormentioning
confidence: 99%
“…According to Liu and Arnett (2002), more than twenty-five million children in the U.S. are on the Internet, therefore site owners should more actively address privacy protection related to children. Congress passed the Children's Online Privacy Protection Act (COPPA) in 1998, setting rules for online collection of information on children (Bowie and Jamal, 2006).…”
Section: Privacy Protection Titlementioning
confidence: 99%
“…Use of privacy policy statements to increase perceived trustworthiness is a relatively new phenomenon, and examination of their use and implications is just beginning to be explored (Criswell & Meinert, 2003;Culnan, 1999;Grewal, Munger, Iyer, & Levy, 2003;Liu & Arnett, 2002;Luo & Najdawi, 2004;Meinert, Peterson, Criswell & Crossland, 2006;Miyazaki & Fernandez, 2000;Pennington et al, 2003;Ranganathan & Ganapathy, 2002). While much of the research to date on this topic has focused on chronicling rates of utilization and variability in content, a few studies have examined the efficacy of privacy statements.…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Kirk (2002) investigated the privacy policies of the Fortune 500 Websites and found that slightly more than fifty percent had privacy policies in place. Much fewer had basic elements of privacy policies, such as assurances that the data collected is secure, allowing people to access data collected about them, providing people with a choice to choose or use their information, and providing notice prior to collection of data.…”
Section: Prior Comparative Research On Privacymentioning
confidence: 99%